(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The effect of modification of some selected MS nutrientmedium on in vitro growth and development of papaya (Carica papayaL.) shoot tips was examined with the objective of optimizing shootregeneration and rooting efficiencies. Modifications were made onselected components of MS medium. Shoot tip explants were obtainedfrom in vitro-grown plantlets. The results showed that MS salts at thetwice full strength was optimal for all parameters measured comparedwith other strengths tested. Sucrose concentrations of 0.75% and 1.5%were better than the other concentrations tested for growth anddevelopment of cultured shoot tips, and there was no significantdifference between them. The results revealed the importance of inclusionof BA and NAA in the nutrient medium at relatively low concentrations,the best results for shoot and leaf formation was recorded with thecombination of BA at 1.0 mg /litre and NAA at 0.01mg /litre, where thegreatest number of shoots and leaves was obtained. The combinationtreatment of 0.3 mg/litre BA and 0.00 mg/litre NAA recorded the bestresults for mean shoot elongation, compared with the other combinationtreatments tested. However, the produced roots were morphologicallyabnormal. The study attested to the essentiality of IBA for rooting of invitro produced papaya shoots, and the data suggested the conduction ofadditional studies for determination of optimal concentration for rooting